Aesthetic full-mouth oral rehabilitation of a young adult with amelogenesis imperfecta: a clinical report - Derya Özdemir Doğan; Fatih Sarı; Onur Şahin (Cumhuriyet University, 2014)
Amelogenesis imperfecta (AI) encompasses a complicated group of hereditary conditions that cause developmental alterations in the structure of the enamel in the absence of a systemic disorder. AI primarily affects the quality and/or quantity of dental enamel, and it may affect all or only some of the teeth in the primary and/or permanent dentition. Treatment of a patient with amelogenesis imperfecta (AI) presents a real problem from both functional and esthetic points of view. An esthetic result also will result in an improvement in the patient's quality of life. This clinical report illustrates the oral rehabilitation of a 23-year-old woman diagnosed with hypomature type of AI. The aim of treatment was to both restore esthetics and improve masticatory function. Aesthetic and functional expectations were met zircon- ceramic restorations.